POTENSI WISATA RELIGI MASJID KERAMAT DI DESA KALIWULU KECAMATAN PLERED KABUPATEN CIREBON: (The Potential Of Religious Tourism Of The Sacred Mosque In Kaliwulu Village, Plered District, Cirebon Regency) - Putri Oktafiani; Ilham Syah Prayoga; Noviyanti; Siti Aliyah; Abdurrohman; Handoko; Anih Sumiati (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2022)
Religious tourism is a tour that is closely related to the religious side. Usually this religious tourism is interpreted as tourism activities to a place such as a place of worship that has advantages such as history, myths and legends that develop. Kaliwulu village comes from the word kali which means river and wulu which is a change in pronunciation from ablution. Kaliwulu Village is located in Plered District, Cirebon Regency. One of the tourism potentials of Kaliwulu village is the Kaliwulu Sacred Mosque. According to legend, the history of the Kaliwulu Sacred Mosque was originally located in the Silintang area but then moved magically to the village of Kaliwulu, precisely on Kauman Street. Research objectives: This activity aims to make the Kaliwulu Sacred Mosque a place for religious tourism and is better known by the wider community. Methods: Data collection methods were carried out by training and descriptive qualitative through interviews with the kuncen of sacred mosques, observations, and documentation of each activity carried out. Results: There was an increase in visits to the Kaliwulu Sacred Mosque after the publication of the Kaliwulu Sacred Mosque through social media. In addition, the facilities and infrastructure of the Kaliwulu sacred mosque have become more adequate and the cleanliness has increased with this activity. So that the activities carried out by this researcher can attract tourists to visit the Kaliwulu Sacred Mosque which has the potential to become this religious tourism. Conclusion: It can be concluded that the Kaliwulu Sacred Mosque has the potential to be used as a religious tourism object in Kaliwulu, Plered District, Cirebon Regency with a very unique history that attracts tourists to visit. Keywords: Tourism, Religion, Sacred Mosque, Kaliwulu